Thermal analysis of Fe2O3 - myristic acid nanocomposite for latent heat storage. (2021) - Santhosh, Sharon; Satish, Malvika; Yadav, Apurv; Anish Madhavan, Asha
Abstract: Phase change materials (PCM) are commonly utilized materials in latent heat energy storage (LHES) systems. In the present study, Fe2O3 was incorporated into myristic acid. The composites were prepared by melting and mixing method. The acids dispersed with Fe2O3 were prepared to enhance the thermal properties of the PCM mixtures and heat transfer at various nanoparticle loadings of 1 wt%, 2 wt%, 3 wt%, and 4 wt% were investigated. It was observed from the experimental results that the duration of melting and cooling rates for PCM composites increased in all nano compositions with respect to the pure myristic acid. Fourier transform infrared spectrum confirmed higher chemical stability of the nanoenhanced phase change material.